Drivers of Employee Performance: The Role of Institutional Support in Elevating Career Growth - Mursidah, Siti; Khoiruddin, Moh; Septantri, Lidiadni (Management Analysis Journal, 2025)
This study aims to analyze the relationship between scientific publication productivity and the academic promotion of lecturers. Scientific publication productivity is a crucial indicator of academic performance, making it important to explore the factors that influence lecturers’ publication productivity to design more effective strategies for improving the quality and quantity of publications. This quantitative study involved 112 lecturers (15% of those promoted in the last five years), using surveys and secondary institutional data. Regression analysis was used to examine the effect of scientific publication productivity on academic promotion, and the data were analyzed using descriptive and statistical methods. The results show that institutional support is the strongest factor influencing academic promotion. Institutional support, research experience, and publication quality significantly affect scientific publication productivity. Moreover, publication productivity mediates the relationship between institutional support and publication quality with academic promotion. These findings imply that improving academic promotion at the local level requires two key strategies: strengthening institutional support and enhancing scientific publication productivity.